Neurovascular compression of medulla oblongata - Association for gestation-induced hypertension - Tanrikulu, Levent; Naraghi, Ramin; Ernst, Veronika; Voigt, Franziska; Hastreiter, Peter; Dörfler, Arnd; Buchfelder, Michael; Beckmann, Matthias; Goecke, Tamme W. (Medical Hypotheses, 2015)
Patients with essential hypertension may show neurovascular compression (NVC) at the rostral ventrolateral medulla oblongata (RVLM). Ectatic loops of the vertebral artery (VA) or the inferior posterior cerebellar artery (PICA) cause NVC. This study aims to show the existence and morphology of NVC in patients with gestation-induced hypertension. 17 females were prospectively examined between 19. +. 0 and 35. +. 6. weeks of gestation. 3 patients with chronic hypertension (group A), 10 patients with preeclampsia (group B), 3 patients with superimposed preeclampsia (chronic hypertension with preeclampsia; group C) and one normotensive patient were included. Groups B and C represented patients with gestation-induced hypertension. All 17 patients underwent imaging by high resolution magnetic resonance imaging (MR-CISS, constructive interference in the steady state). Image processing was done with segmentation and three-dimensional (3D)-visualization was implemented with direct volume rendering of the individual neurovascular details of each patient. 9 of 17 patients (53%) showed NVC of the RVLM. Right-sided NVC was seen in 7 patients (41%). Left-sided NVC was seen in 6 patients (35%). Bilateral NVC was seen in 4 patients (24%). NVC was missing in 8 of the examined 17 patients (47%). The existence of NVC with high-resolution MRI was analyzed in gestation-induced hypertensive pregnant females for the first time. Neurovascular conflicts were seen in hypertensive pregnants. It is possible that NVC is potentially associated in patients with gestation-induced hypertension.
CRIS-Team Scopus Importer:2022-08-05